2013
DOI: 10.5535/arm.2013.37.6.901
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Supernumerary Phantom Limb and Phantom Limb Pain in a Patient With Spinal Cord Injury: Case Report

Abstract: Supernumerary phantom limb (SPL) resulting from spinal cord lesions are very rare, with only sporadic and brief descriptions in the literature. Furthermore, the reported cases of SPL typically occurred in neurologically incomplete spinal cord patients. Here, we report a rare case of SPL with phantom limb pain that occurred after traumatic spinal cord injury in a neurologically complete patient. After a traffic accident, a 43-year-old man suffered a complete spinal cord injury with a C6 neurologic level of inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Phantom limb mainly occurs after amputation and can make patients almost forget that their limbs have been removed, and they can even feel the movement or pain of amputated limbs[9]. Phantom limb has also been reported in SCI patients and has been defined as SPL[3]. In addition to their actual limbs, these patients complain of having extra limbs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Phantom limb mainly occurs after amputation and can make patients almost forget that their limbs have been removed, and they can even feel the movement or pain of amputated limbs[9]. Phantom limb has also been reported in SCI patients and has been defined as SPL[3]. In addition to their actual limbs, these patients complain of having extra limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that virtual feedback has therapeutic effects on the PL following amputation and neurological injury[3,8,12]. Thus, we prescribed for our patient with virtual feedback.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MCA territory CI Arm (1) 6 months +/− Halligan PW [ 34 ] M/65 Rt. BG ICH Arm (1) 3 days −/− Spinal or infraspinal lesion Melinyshyn AN [ 5 ] F/31 PN AIDP Arm (2) Leg (2) 54 days a / a F/57 PN AIDP Arm (2) Leg (2) 72 days +/+ F/68 PN AIDP Arm (2) Leg (2) 46 days +/+ Belgrade M [ 7 ] M/58 PN NS Toe (1) a +/+ Katayama O [ 35 ] M/22 SC (C2) TM Arm (2) 2 years −/+ Choi JY [ 36 ] M/43 SC (C6) TM Leg (2) 6 days −/+ Curt A [ 23 ] M/71 SC (C3) TM Arm (2) 7 days +/+ Sakagami Y [ 6 ] F/31 SC (C4) SjS Arm (1) a −/+ a It was not described in the literature b The number of SPL fluctuated …”
Section: Discussionmentioning
confidence: 99%